2018
DOI: 10.1097/hcr.0000000000000202
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Determinants of Weight Loss Among Young Adults With Overweight and Obesity

Abstract: Among young adults with overweight and obesity who have higher DT, PA appears to be more important to WL than caloric restriction, particularly in males.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…Increasing evidence suggests that psycho‐social eating traits are strong predictors of adult weight gain . Three well‐established eating traits are cognitive restraint ( CR ), disinhibition ( DI ) and hunger ( HU ) .…”
Section: Introductionmentioning
confidence: 99%
“…Increasing evidence suggests that psycho‐social eating traits are strong predictors of adult weight gain . Three well‐established eating traits are cognitive restraint ( CR ), disinhibition ( DI ) and hunger ( HU ) .…”
Section: Introductionmentioning
confidence: 99%
“…[26] 5 Associations between overweight and psychosocial factors have been inconsistent, with some studies reporting an inverse relationship between BMI and selfesteem, and others showing no association. [27][28][29][30] Some of the postulated reasons for the divergent findings include methodological differences in measuring selfesteem, differences in samples surveyed (clinical and nonclinical groups), and in sociodemographic profiles. Previous studies have found that taller adults tend to enjoy better mental health than their counterparts of average and below-average stature.…”
mentioning
confidence: 99%